Correlation Between Cranial Base Morphology and Skeletal Maloclusion in a Sample of Sudanese Orthodontic Patients - Alaa Abd Elgadir Ahmed; Amal Hussein Abuaffan (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Objective: This study aimed to evaluate the relationship between the cranial base and jaw base in a sample of Sudanese orthodontic patients.  Material and methods: one hundred and twenty lateral Cephalograms from university of Khartoum orthodontic department archive 60 males, 60 females, age 18.3 ± 4.3 years old, were classified into 3 sagittal malocclusion groups (40 individuals each) according to their ANB angle. A cephalometric analysis of the study variables of the cranial base (NSBa, N-S, S-Ba, N-Ba) and jaws bases (SNA, SNB, ANB, A-Co, Gn-Co) was carried out, the morphological characteristics of the cranial and jaw bases in the three groups were compared using One-way ANOVA test and Pearson's coefficient correlation analysis.  Results: Cranial base angle and cranial base lengths did not show significant differences between the main classes of malocclusion studied. However, jaw size was statistically significant different between the 3 groups, longer maxilla was found in Class II group and the mandible was longer in Class III group. Strong significant relation was found between SNA, SNB and NSBa in the three groups. Positive correlation was found between cranial base lengths and maxillary and mandibular lengths among the three groups.  Conclusion: Cranial base angulation and lengths has no major role in developing malocclusion.